To the Surface and Back: Exo- and Endocytic Pathways in Trypanosoma brucei - Link, Fabian; Borges, Alyssa R.; Jones, Nicola G.; Engstler, Markus (Frontiers in Cell and Developmental Biology, 2021)
Trypanosoma brucei is one of only a few unicellular pathogens that thrives extracellularly in the vertebrate host. Consequently, the cell surface plays a critical role in both immune recognition and immune evasion. The variant surface glycoprotein (VSG) coats the entire surface of the parasite and acts as a flexible shield to protect invariant proteins against immune recognition. Antigenic variation of the VSG coat is the major virulence mechanism of trypanosomes. In addition, incessant motility of the parasite contributes to its immune evasion, as the resulting fluid flow on the cell surface drags immunocomplexes towards the flagellar pocket, where they are internalized. The flagellar pocket is the sole site of endo- and exocytosis in this organism. After internalization, VSG is rapidly recycled back to the surface, whereas host antibodies are thought to be transported to the lysosome for degradation. For this essential step to work, effective machineries for both sorting and recycling of VSGs must have evolved in trypanosomes. Our understanding of the mechanisms behind VSG recycling and VSG secretion, is by far not complete. This review provides an overview of the trypanosome secretory and endosomal pathways. Longstanding questions are pinpointed that, with the advent of novel technologies, might be answered in the near future.